Analysis of classifications of types of the systems of information security - Юдін, О. К.; Бучик, С. С. (Problems of Informatization and Control, 2015)
In the article the further improvement of typical chart of information protection is carried out takinginto account the method of the «Double three of protection» worked out by the authors. It is shownthat the typical chart of protection can be taken as a basis for further development of systems ofprotection of state informative resources. General classification of types of systems of informationprotection taking into account the conducted analysis on this question is brought, the necessity of theuse of the principle of complexity of protection of state informative resources is shown